PENDAMPINGAN EKSTRAKURIKULER KOMPUTER BERBASIS DESAIN DIGITAL DENGAN FIGMA DI SMA KOLESE DE BRITTO - Rini, Maria Nila Anggia; Prabawati, Andhika Galuh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2025)
This community service activity aims to improve students' digital design skills through a project-based learning (PBL) approach. This service was carried out to fill extracurricular computer activities for class X and XI SMS Kolose De Britto students. The focus of the activity is teaching students to design applications, especially using Figma tools, a web-based design tool. This activity was carried out in 11 meetings, consisting of 6 material sessions, 3 project work sessions, and 2 evaluation sessions. The results of the activity showed an increase in students' technical skills, especially in understanding design flow, team collaboration, and utilizing Figma features to create relevant LMS prototypes. The final product is an LMS prototype with features that support learning, such as materials, assignments, grades, attendance, schedules and academic calendars. This activity has a positive impact in the form of increasing students' knowledge in digital design, creativity and teamwork skills. Reflections on the implementation of activities show that the PBL method is effective in encouraging students to learn actively and applied.